JEJAK LANGKAH SURAU: EVOLUSI PENDIDIKAN ISLAM DARI TRADISI LOKAL HINGGA TANTANGAN MODERN DI SUMATERA BARAT - Mufti, Zaki Aulia; Samad, Duski; Mamad, Firdaus Sutan; Kurnia, Asraf; Desfitri, Eni (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study explores the evolution of surau as a traditional Islamic educational institution in West Sumatra across different historical periods. The surau played a crucial role as a center for religious instruction and character formation within Minangkabau society. However, socio-political and educational developments have led to functional and structural transformations. Employing a qualitative approach with a descriptive-historical design, the research was conducted in key regions such as Padang Panjang, Bukittinggi, Payakumbuh, and Agam. Data were collected through literature reviews, field observations, and in-depth interviews with community leaders, surau caretakers, and alumni. The findings reveal that the surau has shifted from an informal, community-based educational center to an institution increasingly integrated into formal Islamic education, such as madrasahs. Although no longer structurally dominant, the surau continues to serve as a hub for spiritual guidance and local cultural values. This study recommends revitalizing the role of the surau to complement modern Islamic education, especially in response to the challenges of globalization and the erosion of value-based frameworks within formal education systems.